Upper limb joint dynamics during manual wheelchair propulsion - Desroches, Guillaume; Dumas, Raphaël; Pradon, Didier; Vaslin, Philippe; Lepoutre, François-Xavier; Chèze, Laurence (Clinical biomechanics (Bristol), 2010)
Inverse dynamic methods have been widely used to estimate joint loads during manual wheelchair propulsion. However, the interpretation of 3D net joint moments and powers is not always straightforward. It has been suggested to use joint coordinate systems (expression of joint moment on anatomical axes) and the 3D angle between joint moment and angular velocity vectors (propulsion, resistance or stabilization joint configuration) for a better understanding of joint dynamics. Nine spinal cord injured subjects equipped with reflective markers propelled in a wheelchair with an instrumented wheel. Inverse dynamic results were interpreted using joint coordinate systems, 3D joint power and the 3D angle between the joint moment and joint angular velocity vectors at the three upper limb joints. The 3D angle was used to determine if the joints were predominantly driven (angle close to 0 or 180 degrees) or stabilized (angle close to 90°). The wrist and elbow joints are mainly in a stabilization configuration (angle close to 90°) with a combination of extension and ulnar deviation moments and an adduction moment respectively. The shoulder is in a propulsion configuration, but close to stabilization (angle hardly below 60°) with a combination of flexion and internal rotation moments. Stabilization configuration at the joints could partly explain the low mechanical efficiency of manual wheelchair propulsion and could give insight about injury risk at the wrist, elbow and shoulder joints.